2000
DOI: 10.1097/00003246-200004000-00043
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of illness severity and length of stay to functional outcomes in the pediatric intensive care unit: A multi-institutional study

Abstract: These data establish current relationships for the POPC and PCPC outcome scales based on multi-institutional data. The reported relationships can be used as reference values for evaluating clinical programs or for clinical outcomes research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
129
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(138 citation statements)
references
References 14 publications
7
129
2
Order By: Relevance
“…2 However, in the study involving 11,104 patients, 576 patients improved, accounting for 5.1% of cases. 12 Oom also found similar results, reporting 6.4% of cases with negative delta-POPC. 4 In common with this study, the overwhelming majority of functional improvement cases were patients in postoperative and liver or kidney post-transplantation care, i.e., patients whose disabilities and/or diseases have been repaired and/or improved by means of surgical operations.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…2 However, in the study involving 11,104 patients, 576 patients improved, accounting for 5.1% of cases. 12 Oom also found similar results, reporting 6.4% of cases with negative delta-POPC. 4 In common with this study, the overwhelming majority of functional improvement cases were patients in postoperative and liver or kidney post-transplantation care, i.e., patients whose disabilities and/or diseases have been repaired and/or improved by means of surgical operations.…”
Section: Discussionsupporting
confidence: 59%
“…12 Volakli et al, in a study evaluating mortality and morbidity among patients 2 years after admission to an ICU, found that 25.8% of the patients had already presented alterations according to the PCPC scale and 40% by the POPC at the time of admission. 19 Cunha et al…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The retrospective nature of this study confined our data collection to what was recorded in the charts, and may contain unavoidable bias / residual confounders. It would have been preferable to have long-term outcome data such as 3, 6 and 12 month GOS or the Fiser scores (26,27) to assess the impact of hypotension. Unfortunately, there is currently no large or national pediatric database that contains serial hemodynamic data from the field through PICU discharge for a set of patients, making the present relatively small study valuable.…”
Section: Limitationsmentioning
confidence: 99%
“…As a consequence, patients with neurodevelopmental disabilities need to be treated in intensive care units more often than other patients. 13 In spite of the need for more serious treatment, the functional status of children with neurodevelopmental disabilities at their discharge from PICU was 4,10 Hence, in spite of differences between the units in populations of patients managed and available specialties, the POPC scale has shown to be a simple and accurate tool for assessment of outcome in intensive care units. It is, therefore, advisable to use it regularly as a means of evaluating health care quality in pediatric intensive care.…”
Section: -17mentioning
confidence: 99%